Sistem Pendukung Keputusan Pemilihan Hotel Terbaik Di Kota Medan Menggunakan Metode EDAS - Siti Cholijah Sitompul; Reza Nadza; Ferryanto Sihotang; Tengku Syahputra; Arief Budiman (LKP Unity Academy, 2025)
The rapid development of technology has impacted various sectors, including tourism. Medan, as one of the metropolitan cities in Indonesia, has experienced a significant increase in tourist visits, leading to heightened competition among hotels. This study aims to develop a decision support system (DSS) for selecting the best hotel in Medan using the EDAS (Evaluation Based on Distance From Average Solution) method. This method was chosen for its ability to assess alternatives based on their distance from the desired average solution, in accordance with relevant criteria. The study considers five criteria in hotel selection: price, location, hotel rating, facilities, and room type. As a sample, five popular hotels in Medan were used for the analysis. In the calculation using the EDAS method, a decision matrix is first created based on the weighted values of the criteria. Then, the average value for each criterion is calculated, followed by the computation of positive and negative distance matrices for each alternative. The results show that the EDAS method can assist in making objective and measurable decisions to select the best hotel, based on user preferences that take into account various aspects such as price and facilities. This study is expected to contribute to the development of DSS for the hotel industry, particularly in Medan, in order to enhance tourists' experience in choosing a hotel that suits their needs and budget.